Transnationalism as the antidote of corruption in ASEAN region: SEA-PAC - Aryowiloto, Julang (Journal of Integrative International Relations, 2024)
Corruption is a serious problem which happened transnationally in almost every single country in the world including ASEAN countries. Based on CPI rank, six of ASEAN countries are part of fifteen most corrupt countries in Asia Pacific region. It means that corruption is a challenge that ASEAN country need to face together related to region development. Consciousness of collective responsibility namely corruption eradication then brings ASEAN to a model of transnationalism which is the establishment of an international organization called SEA-PAC. This study analysis starts from review about SEA-PAC historically and the logic of transnationalism which provides a necessary background for its operation. After that, this study elaborates the performance of SEA-PAC since the beginning like how many corruption cases have handled and how much asset has saved by SEA-PAC in ASEAN region. In the next level, this study measures the prospect of SEA-PAC based on its performance. Whether SEA-PAC as a tangible form of transnationalism in ASEAN need to be maintained or on the contrary need to be changed by another mechanism which more effective. In the end, this study provides a conclusion by argument confirmation about how important SEA-PAC in order to ASEAN region development.